Assessing the Impacts of the COVID-19 Pandemics on Sustainable Development Goals in Nepal - Joshi, Toyanath; Poudel, Rudra Prasad; Kafle, Kamana; Bhattarai, Bandana; Prasai, Benu Prasad; Adhikari, Santosh (Frontiers in Sustainable Food Systems, 2022)
Globally, billions of people and their livelihood are threatened by the onset of COVID-19. In Nepal, resource-poor people who lost their job were the hardest hit among millions of impacted populations. Further, the associated effects of pandemics are food supply chain interruption and people’s inferior physical and mental wellbeing. The consequence is achieving the Sustainable Development Goals (SDG), especially No Poverty (SDG1) and Zero Hunger (SDG2), are in doubt. Yet no scientific studies available to see COVID-19 and SDGs relationships in Nepal, government reports and macroeconomic updates indicated that COVID-19 is likely to deter significantly in achieving SDGs targets. This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines to quantify the impacts of the COVID-19 pandemic in Nepal’s macro-economy from March 2020 to December 2021. Our study indicated that the COVID-19 exerted inevitable challenges in achieving SDGs targets in terms of food security and household poverty. Therefore, this paper recommended creating more employment opportunities in the domestic economy and establishing a resilient food system.